Identification and validation of roles of lysyl oxidases in the predictions of prognosis, chemotherapy and immunotherapy in glioma - Xia, Qin-Xuan; Yu, Jing; Wang, Zhao-Jun; Guan, Qi-Wen; Mao, Xiao-Yuan (Frontiers in Pharmacology, 2022)
Graphical Abstract